Achieving Educational Service Quality by applying international standard (ISO21001:2018) case study / university of technology – electromechanical engineering department – energy branch - حافظ عبد الناصر علك; ابراهيم حنان مازن (Journal of Economics and Administrative Sciences, 2019)
The research examines the mechanism of application of )ISO 21001: 2018( in the Energy Branch- Electromechanical Engineering at the University of Technology to achieve the quality of the educational service to prepare the branch to obtain the certificate of conformity with the requirements of) ISO 21001: 2018(, the necessary data were collected Depending on the (CHEKLIST) of (ISO 21001: 2018), field interviews and records of the concerned department, The researchers reached a number of results, the most prominent of which was the adoption of high quality leadership leaders and their willingness to implement the standard requirements, The university has a basic structure that qualifies it to implement the international standard, as well as an overlap in the planning process of the department’s quality management system.